Presentation Dossiê: Translation in teaching and learning foreign languages - Evangelista, Maria Cristina Reckziegel Guedes; Pinto, Paula Tavares; Nadin, Odair Luiz (Revista EntreLinguas, 2017)
The journal EntreLínguas aims at “Publishing articles, reports, critical reviews and interviews by national and international researchers about language teaching and learning of modern foreign languages (MFL), with the aim of promoting a debate on the theoretical and methodological processes of teaching of MFL”.